Mentorship in Teacher Education Programs: A Review of Practices, Outcomes, and Challenges - Mwesigwa, Felix; Nakato, Nalukenge (Acta Pedagogia Asiana, 2026)
Mentorship in teacher education plays a vital role in the development of pre-service teachers by bridging the gap between theoretical knowledge and practical application. Effective mentorship fosters professional identity, enhances classroom management skills, and promotes long-term career satisfaction. This review aimed to explore the different models of mentorship in teacher education, their outcomes, challenges, and enablers to identify best practices and provide evidence for improving mentorship programs. A systematic review was conducted using databases such as ERIC, Scopus, and JSTOR. Inclusion criteria focused on peer-reviewed articles published between 2013 and 2024, with a specific focus on teacher education programs. Studies examining mentorship models, outcomes, and challenges were considered. The review identified several mentorship models, including traditional dyadic mentorship, peer and group mentoring, and online/e-mentoring. Key outcomes of mentorship include professional identity development, enhanced instructional skills, and increased teacher retention. Challenges, such as time constraints, mentor overload, and mismatched mentor-mentee pairings, were prevalent. Enablers like structured mentor training and reflective practices emerged as critical for successful mentorship programs. Findings highlight the need for structured, evidence-based mentorship programs in teacher education to improve teacher preparation and retention. Future research should focus on longitudinal and cross-cultural studies to explore the long-term effects of mentorship. This review contributes to the development of mentorship models that can be implemented to support teacher growth and retention globally.